2020
DOI: 10.1111/ddi.13136
|View full text |Cite
|
Sign up to set email alerts
|

Climate change exposure and vulnerability of the global protected area estate from an international perspective

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…Our analyses suggest that the current PA network is too small and poorly connected to provide resilient protection for many mammalian species. We estimate that most underprotected species have a viable protected population in only one or two countries or ecoregions and will therefore be particularly vulnerable to perturbations such as climate change, disease outbreaks ( 63 , 64 ), changes in public policy priorities and the downgrading of PAs ( 29 ), major societal transformations such as warfare ( 30 ), or economic downturns. The COVID-19 pandemic, for example, has resulted in widespread loss of tourism revenue to African PAs, potentially reducing management effectiveness and the ability to support local livelihoods ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses suggest that the current PA network is too small and poorly connected to provide resilient protection for many mammalian species. We estimate that most underprotected species have a viable protected population in only one or two countries or ecoregions and will therefore be particularly vulnerable to perturbations such as climate change, disease outbreaks ( 63 , 64 ), changes in public policy priorities and the downgrading of PAs ( 29 ), major societal transformations such as warfare ( 30 ), or economic downturns. The COVID-19 pandemic, for example, has resulted in widespread loss of tourism revenue to African PAs, potentially reducing management effectiveness and the ability to support local livelihoods ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also broadly consistent with previous studies which examine climate change exposure of protected areas globally. For example, Hoffmann and Beierkuhnlein 20 showed that climate change exposure in PAs was projected to be most pronounced in tropical and subtropical regions. Our findings suggest these areas, along with northern mid-latitude regions, which have the least PA coverage and greatest human footprint, are poised to transition to other ecoregions and biomes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…If the past is prologue, species assemblages and ecosystems will change over time, driven by species range shifts, shifts in abundance, and extirpation or extinction [17][18][19] . A growing body of research suggests that terrestrial lands within the protected area estate 16,20 and globally are experiencing heightened climate change exposure 21 and relatively novel climatic conditions 22 . These changes and those projected for the future are expected to result in changes in the extent of biomes [23][24][25] and habitat transformation in terrestrial ecoregions globally 26 .…”
mentioning
confidence: 99%
“…Identifying areas where species that are most exposed to climate change will occur in forthcoming decades has become a priority for conservation planning (Carroll et al, 2017; Heller et al, 2015; Wang et al, 2018). The dynamically shifting climate is a major parameter driving the global redistribution of biodiversity, and is expected to force many species out of current reserves, jeopardizing the efficiency of the present, static network of protected areas (PAs), which were established to halt biodiversity declines (AraĂșjo et al, 2011; Hoffmann & Beierkuhnlein, 2020). Therefore, it is necessary to prioritize conservation actions and policies that incorporate future conservation challenges and mitigate the effects of climate change (Carroll & Noss, 2021; Mace et al, 2018).…”
Section: Introductionmentioning
confidence: 99%